2010
DOI: 10.1260/1747-9541.5.2.281
|View full text |Cite
|
Sign up to set email alerts
|

The Team-Mate Identification (TM-ID) Test: Effect of Participant and Situation Familiarity on Response Accuracy and Latency

Abstract: In field and pool sports, players' running or swimming motor patterns appear to characterise them, and these ‘gait signatures' may aid in identifying players as team-mates. If this identification process was sufficiently brief to be relevant in ball sports, training to improve familiarity with team-mates' movement patterns may improve team performance. We examined time for Team-Mate Identification (TM-ID) decisions under different circumstances. 6 water-polo players (team-mate participants) and 6 club swimmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Furthermore, subsequent studies demonstrated that athletes had the capacity to perform this task in sport relevant time (<500 ms; Steel, Adams, Canning, & Eisenhuth, 2010;Steel & Dogramaci, 2015). In each study, participants displayed significantly above chance levels for discrimination accuracy, although some members performed close to chance.…”
Section: A Sport Science Research Explanation For Perceptual Ability mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, subsequent studies demonstrated that athletes had the capacity to perform this task in sport relevant time (<500 ms; Steel, Adams, Canning, & Eisenhuth, 2010;Steel & Dogramaci, 2015). In each study, participants displayed significantly above chance levels for discrimination accuracy, although some members performed close to chance.…”
Section: A Sport Science Research Explanation For Perceptual Ability mentioning
confidence: 99%
“…The identification of such personnel can be accomplished by using simple testing methods, such as those used by Steel et al, (2010). Video footage of teammates and nonteammates were temporally occluded and formulated a randomized sequence whereby observers used a latency device to indicate teammate affiliation and confidence in this decision.…”
Section: Testing Visual Biological Motion Perception Abilitymentioning
confidence: 99%
“…the present aim was to evaluate whether liking for a teammate influenced the temporal aspects of decision making in the Teammate Identification (TM-ID) Test (Steel, et al, 2010). Whereas in previous research, head-down swimmers were filmed from above, in the current research water-polo players (teammate participants) and club swimmers (unknown distractors) were filmed from below the water line, performing a straight-line, head-down, sprint swim.…”
mentioning
confidence: 90%
“…of viewing for swimming water-polo players (Steel, et al, 2006). A subsequent study (Steel, Adams, Canning, & Eisenhuth, 2010) demonstrated that these decisions could be made in less than 500 msec., which is fast enough to be relevant in sport. Furthermore, this perception was related to the duration of time the teammates had trained together.…”
mentioning
confidence: 97%
See 1 more Smart Citation